Calvin and Hobbes - Watterson, Bill (Kansas City, Missouri : Andrews McMeel Publishing, 1987)
A collection of comic strips following the adventures of Calvin and his stuffed tiger Hobbes.
Keywords: Calvin and Hobbes (Comic strip)